PERANAN ETIKA DALAM LINGKUNGAN KERJA : Array - Sahadi; Otong Husni Taufiq; Ida Farida (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
This article is entitled The Role of Ethics in the Work Environment. In a work environment, a person is expected to have a strong work ethic. A strong work ethic is a set of values or norms that are closely held by everyone as an employee or as a manager, which regulates the regulations at work. Ethical standards differ from the core values of one organization to another. Ethical standards can be a true reference for the progress of an organization or work environment. The research method used is descriptive analysis method, namely by describing in general the facts found, then analyzed based on the theories put forward by experts that are related to the problem to be studied. Work ethics plays a very important role in the work environment, including: (1) Assessment of human behavior, (2) Assessment of work results, (3) Control tools, (4) Signs, (5) Cross-check in overcoming difficulties morals, (6) fundamental principles, and (7) guidance towards a good directio